(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Many decades after the first patients were treated with antibiotics, bacterial infections have again become a threat. To mitigate the risk of antibiotic resistance, scientists now consider plant secondary metabolites to be a major organic antibacterial substitute. Mentha arvensis is widely used both as a culinary spice and as an important remedy in Armenian traditional medicine. Over 40 components were identified in the investigated extract by Ultra High-Performance Liquid Chromatography (UHPLC). Among the identified components are coumarins (3 components), organic acids (around 11 components), flavan-3-ols (2 components), stilbene (1 component), flavonols (3 components), and flavones (around 10 components). Current research emphasizes the antibacterial properties of Mentha arvensis. The bacterial strains used in this study included both gram-negative and gram-positive bacteria: Escherichia coli K12, ampicillin-resistant E. coli DH5a-pUC18, kanamycin-resistant E. coli pARG25, Salmonella typhimurium MDC 1754, Bacillus subtilis WT-A1, and Staphylococcus aureus MDC 5233. The disk-diffusion method (Kirby-Bauer antibiotic testing) was employed to assess the initial antimicrobial activity and estimate in vitro antimicrobial susceptibility. M. arvensis extract (MAE) formed bacterial growth inhibition zones ranging in size: 4.0-6.0 mm in the case of B. subtilis, 4.0-5.0 mm for E. coli DH5a-pUC18, and 3.0-4.0 mm for E. coli K12. Origanum exhibited no inhibitory effect on any tested bacteria in this test. MTT was performed to evaluate bacterial susceptibility to antibiotics after the treatment with MAE. The results indicated that the investigated extract showed no effect on kanamycin-resistant E. coli. However, it (0.25 mg/mL) reduced the MIC of ampicillin for E. coli DH5a-pUC18 by sixfold, and fourfold at the concentration of 0.125 mg/mL. To elucidate the potential mechanisms of the antibiotic activity of tested extract, the changes in H+-fluxes across the cell membrane in ampicillin-resistant E. coli were explored. According to the results, MAE does not have any significant influence on the total proton flux of the reference strain, meanwhile, the extract reduces the flux twice in the resistant strain, indicating the influence of extract components on membrane-associated properties of bacteria.